2010
DOI: 10.1080/01431160902882512
|View full text |Cite
|
Sign up to set email alerts
|

The relation of chlorophyll-a concentration with the reflectance peak near 700 nm in algae-dominated waters and sensitivity of fluorescence algorithms for detecting algal bloom

Abstract: In order to investigate the relation of chlorophyll-a concentration with the reflectance peak near 700 nm, reflectance spectra of harmful algal bloom (HAB) species and non-HAB algae were obtained based on in situ measurements in the oceans and cultural tank data. It is found that the fluorescence line heights (FLH) of reflectance spectra and the concentrations of seawater chlorophyll-a have good correlation; their coefficients of determination are larger than 0.86, excepting Ceratium furca and Heterosigma akas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…Since 2002, the moderate resolution imaging spectroradiometer (MODIS) provides declouded 8-day 9 km resolution imagery in 405-877 nm spectral bands that enable a fluorescence line height (FLH) calculation [30]. MODIS FLH is found to be consistent with in situ observations of red tide [31][32][33] as a radiometric index of relative harmful phytoplankton biomass. The European MERIS satellite also has spectral bands across the fluorescence peak capable of detecting red tides and cyanobacteria blooms [34], even in coastal turbid waters [35].…”
Section: Introductionsupporting
confidence: 50%
“…Since 2002, the moderate resolution imaging spectroradiometer (MODIS) provides declouded 8-day 9 km resolution imagery in 405-877 nm spectral bands that enable a fluorescence line height (FLH) calculation [30]. MODIS FLH is found to be consistent with in situ observations of red tide [31][32][33] as a radiometric index of relative harmful phytoplankton biomass. The European MERIS satellite also has spectral bands across the fluorescence peak capable of detecting red tides and cyanobacteria blooms [34], even in coastal turbid waters [35].…”
Section: Introductionsupporting
confidence: 50%
“…Hu et al [2005] demonstrated that MODIS FLH provided more reliable information than the ratio-derived Chl product on the relative distribution of the bloom patches in the complex Florida coastal environment, despite some artifacts in the data and uncertainty attributed to factors such as unknown fluorescence efficiency. This approach was also found valid in China's coastal waters, usually with a doubled value of FLH over the background level as a bloom indicator [e.g., Li et al, 2011;Shang et al, 2012;Zhao et al, 2010].…”
Section: Differentiation Of Dinoflagellate From Diatom Based On R Rsmentioning
confidence: 99%
“…Gower et al (2008) stated that the radiance maximum at 709 nm is indicative of phytoplankton biomass in excess of 30 mg Chla m À3 . In addition, research has shown that the magnitude of the MERIS 709 nm band can be related to Chla-specific concentrations of phytoplankton (Zhao et al, 2010). Unfortunately, no quantitative relationships have yet been established between the MCI and Trichodesmium abundance and warrants further investigation.…”
Section: Lessons Learned From Merismentioning
confidence: 94%